Spacetime and General Relativity: A Novel Approach - Rowland, David (New Trends in Physical Science Research Vol. 4, 2022)
Four-dimensional (Minkowski) spacetime is a mathematical construct with no real-world use. Time is an abstract measurement of motion and sequences of events that happen with the 3-D. It is not possible to extract nonphysical time from the 3-D and project it onto a fourth supposedly physical axis with an independent set of reference points. Spacetime does not exist, does not curve, and does not interact with gravity. Because Einstein based his geometric theory of gravity (general relativity) entirely on this false spacetime foundation, general relativity is a fatally flawed theory. Geometry is the mathematics which describes the properties and relations of points, lines, surfaces, and the relative locations of objects. Mathematics is an abstract form of measurement and not a physical thing. Einstein’s geometric theory of gravitation fails because geometry can neither cause nor be influenced by anything that exists in physical reality. General relativity fails because it presumes that a physical force (gravity) interacts with an abstraction (geometry) that has no physical existence. Both Minkowski spacetime and general Relativity are disproved clearly in this chapter.